Diagnostic challenges of neurosarcoidosis in non-endemic areas - Shrestha, Keshari; Kleinschmidt-DeMasters, B. K.; Ormond, D. Ryan (Frontiers in Neurology, 2024)
Background Neurosarcoidosis (NS) is a challenging diagnosis, particularly when cases occur in low-prevalence, non-endemic geographic regions. In the United States, the highest incidence is in the Midwest and Northeast, compared to our Southwest location. While it is well known that NS may clinically and neuroradiographically mimic meningeal carcinomatosis, autoimmune or infectious pachymeningitis, neurosyphilis, or tuberculosis, diagnosis may be particularly challenging if systemic signs of sarcoidosis are lacking or unconfirmed or if dural-based masses are present. We reviewed our Colorado experience with NS cases, focusing our study on cases where NS represented the first histological confirmation of disease. Methods A search of departmental databases was conducted with the search term “neurosarcoidosis” to identify cases 1-2008 to 12-2019, inclusive of the given case numbers. Patients were only included if their clinical and neuroimaging features were unusual and only when a biopsy of the central nervous system (CNS) represented the first confirmed diagnosis of sarcoidosis. Results A total of 17 cases were identified, of which the biopsy of the CNS was used for the initial confirmation of the disease in 9 of them. The most unusual findings were two patients with dural-based masses, one of which had pure NS as the cause of meningioma-like lesions and the second of which had coexistent meningioma and intimately admixed non-necrotizing granulomas of NS. Conclusion NS with unusual features, especially in non-endemic areas, continues to yield diagnostic challenges for neurologists, neuroradiologists, and pathologists.